Study of a Predator-Prey System with Monod-Haldane Functional Response and Harvesting - Gazi, N.H.; Mandal, M.R.; Sarwardi, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present work we study a predator-prey harvesting model with Monod-Haldane functional response. The mathematical features of the model have been analyzed in terms of stability, bifurcations and harvesting. Threshold values for some parameters indicating the feasibility and stability conditions of all equilibria are determined. The range of significant parameters under which the system admits different types of bifurcations are investigated. Optimal harvesting criteria and the net economic revenue are analyzed. Numerical illustrations are performed finally in order to confirm the analytical findings.